Estudo de filtragem de biogás para fins energéticos utilizando como método de filtragem lavador de gases de baixo custo - Canever, Víctor Bruno (2017)
Biogas from anaerobic digestion for energy production proposal has being increasing globally in recent years. Biogas from anaerobic digestion is seen as a good alternative for the production of electric power, heat and fuels. And an almost unanimous goal, worldwide speaking is the research for processes that upgrade biogas into bio methane. The majority of biogas produced in Brazil is used in rural areas as heat source, using in direct combustion or to produce off-grid electric power, and the lack of filtration processes could damage the equipment where the pure biogas are being used. This work studied CO2 and H2S removal from biogas produced from swine`s manure, using a low-cost, and low pressure, water scrubber prototype. It was used three water based solutions as filtering element: pure water, iron sulphate III in water solution at 4,0 g/l (or 0,01mol/l) and sodium carbonate in water solution at 10,0 g/ l (or 0.094 mol/l). Upgrading around 40 % on CO2 and 70 % on H2S were achieved using pure water, upgrading around 30 % on CO2 and 75 % on H2S were achieved using iron sulphate III in water solution and an upgrade around 55 % on CO2 and 99 % on H2S were achieved using sodium carbonate in a water solution. The upgrade process efficiency is highly time dependent and a good upgrade results, during the time, were achieved using sodium carbonate in a water solution.